Assessment of Heavy Metals Contamination and Associated Health Risks in the Soil of AL-Khalidiya City, Anbar, Iraq - Bashar Abdulazeez Mahmood; Saja S. Faris; Auday Tariq AlBayati (Basrah Journal of Science, 2026)
This study was used to analyze (11) soil samples collected from the Al-Khalidiya district in Anbar Governorate, Iraq. The technique is the atomic absorption spectrophotometer (AAS) used to analyze soil samples for four heavy metals: Pb2+, Cd2+, Cr3+, and Ni2+. Where heavy metals possibly accumulate in the soil due to petrochemical falls, industrial waste releases, the removal of exceptional quality metal waste, and other processes, which is why this technique was used. The results show that the quantity of heavy metals in each soil sample is between (2.55 – 20.88) mg/kg for Pb+2, (0.13-1.86) mg/kg for Cd+2, (0.051-0.183) mg/kg for Cr+3 and (1.05-6.3) mg/kg for Ni+2. The results of the AAS technique found that the concentration element of lead and nickel is higher than the allowed limits according to WHO in some residential regions, in contrast, the concentration of cadmium is higher than the permitted limits according to WHO in some agricultural areas. The Eri is divided into three primary categories: low, Considerable, and high risk at the soil samples. As found that the Heavy metals pose harmful effect on both children and adult health as HI > 1. High values of Eri brought on by Cd, Ni, Pb and Cr at the various soil samples are the cause of high RI.